A magyar mezőgazdaság környezeti és regionális problémái - Sántha, Attila (Tér és Társadalom, 1996)
It has been hardly more than three decades since Hungarian agriculture abandoned its traditional production model that was very close natural economy. The development and decline of the so-called industry-type model were mainly hindered by a deep crisis induced by politics. Presently the agricultural sector, in which the quality of production and its tools are declining and where the ownerships are chaotic, thus the whole sector becoming less and less competitive, can only meet the market requirements with the help of conscious central interventions. It is important, among other things, because only a dynamically developing sector producing with up-to-date machinery can meet the criteria of environmental and natural protection and also of human health and veterinary hygiene which the society and also the markets expect of agriculture. in Hungary the traditional model contributed to the worsening of the hamis with its lack of machinery and poverty, whereas the industry-type model with its extremes and mechanical attitude. Although these latter were significant, they were not as serious as in many developed countries, for the short period of existence of the industry-type model. The biggest problem at the moment is the fact that the Hungarian agriculture is caught in this model because of its crisis, while Western Europe has already left it behind. A run-down sector not only becomes uneconomical but also harmful for the environment. Even in the absence of the necessary tools, the survival of the mechanical, industry-like attitude is a serious problem, demonstrated by the irresponsible use of lands, the abuses in the field of plant protection and the increasing number of stubble-fires.